Remote Sensing and Geographic Information System (GIS) based runoff estimation from an agricultural watershed - MISHRA, PURNIMA; BABU, R. RAVI (Journal of Soil and Water Conservation, 2022)
Bhalukanala agricultural watershed falling in the upper catchment of Dwarakeswar River in the West Bengal state of India was selected for the present study. The rainfall and corresponding runoff from the watershed for selected storm events during the monsoon period of three consecutive years were collected through field observations. Remote sensing and GIS were used in the generation and integration of different thematic maps particularly the land use and cover and Hydrologic Soil Group (HSG) for deriving Curve Number (CN), which is used in the estimation of runoff. A close agreement was found between observed and simulated runoff, signifying the capability of the Soil Conservation Service – Curve Number (SCS-CN) model for estimation of runoff using remote sensing and GIS for the design of soil and water conservation structures in different ungauged watersheds in laterite zone of West Bengal state of India.